2013
DOI: 10.1111/j.1741-3729.2012.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiracial Children and Poverty: Evidence From the Early Childhood Longitudinal Study of Kindergartners

Abstract: Despite the recent growth in multiracial children among American children, we know very little about their well‐being. Using the Early Childhood Longitudinal Study, Kindergarten Class (N = 17,706), we evaluated the likelihood of living in poverty and near poverty for multiracial and monoracial children. Most multiracial groups have poverty or near poverty rates that are in between Whites and their respective minority monoracial counterparts, with Asian‐Whites reporting a risk of poverty equivalent to Whites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…While single-race identification remains most commonly studied (Davenport 2016), an expanding body of work examines the distinctive social experiences of mixed-race groups. Research on poverty (Bratter and Kimbro 2013;Bratter and Damaske 2013), residential segregation (Bennett 2011;ellis et al 2012), mate selection preferences and behaviors (Qian and Lichter 2007;Currington, Lin, and Lundquist 2015), and physical and mental health (Bratter and Gorman 2011;tabb 2015) have focused on comparisons between single-and multiple-race groups. It is important to note that these studies define racially mixed status in various ways, including parental racial identification as well as self-reporting of racial identification with multiple categories.…”
mentioning
confidence: 99%
“…While single-race identification remains most commonly studied (Davenport 2016), an expanding body of work examines the distinctive social experiences of mixed-race groups. Research on poverty (Bratter and Kimbro 2013;Bratter and Damaske 2013), residential segregation (Bennett 2011;ellis et al 2012), mate selection preferences and behaviors (Qian and Lichter 2007;Currington, Lin, and Lundquist 2015), and physical and mental health (Bratter and Gorman 2011;tabb 2015) have focused on comparisons between single-and multiple-race groups. It is important to note that these studies define racially mixed status in various ways, including parental racial identification as well as self-reporting of racial identification with multiple categories.…”
mentioning
confidence: 99%
“…This expectation rests on the in-between socioeconomic status of interracial couples. Specifically, interracial couples with a NH White partner are generally less advantaged than same-race White couples, but more advantaged than their minority same-race counterparts (Bratter & Kimbro, 2013). This intermediate socioeconomic status may reflect the pooling of resources between a member of a relatively socioeconomically advantaged and a relatively disadvantaged racial/ethnic group.…”
Section: Theoretical Expectations For Family Instability Among Multiracial Childrenmentioning
confidence: 99%
“…Using a "snapshot" approach, Schlabach (2013) found that larger shares of White-Black children lived in single-parent households than their monoracial White and Black peers. Similarly, Bratter and Kimbro (2013) showed that multiracial kindergarteners were less likely than their monoracial peers to have married parents. Raley et al (2019) examined children's family structures over time; however, they combined multiracial children with "other" monoracial children.…”
Section: Previous Findings On Family Instability Among Multiracial Childrenmentioning
confidence: 99%
“…Nevertheless, some have argued that mixed race/ethnicity people suffer less racial discrimination than their non-mixed minority counterparts, because they may appear more white ( Twine & Gallagher, 2008 ), perhaps because they have more flexibility in their management of a racialised identity. In addition, there is some evidence that mixed race/ethnicity children have more favorable socio-economic circumstances than their non-mixed minority peers ( Bratter & Kimbro, 2013 ; Panico & Nazroo, 2011 ). Both more favorable socio-economic circumstances and reduced exposure to racism and racial discrimination are likely to result in improved socioemotional wellbeing ( Kelly, Becares, & Nazroo, 2013 ; Priest et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here it is worth noting that concerns have been expressed about the generalizability of existing findings. As Cooney and Radina (2000) have noted, much of the research, although not all ( Bratter & Kimbro, 2013 ), has been limited to clinical settings, generating the presentation of troubled mixed race/ethnicity children who struggle with identity formation and who have socioemotional problems in their families, schools, and communities. This is aggravated by the failure of some studies to include comparisons between mixed race/ethnicity children and their non-mixed counterparts.…”
Section: Introductionmentioning
confidence: 99%